Implikasi Hukum Internasional Terhadap Sengketa Kepemilikan Data Digital Antara Negara dan Korporasi Global - Javan Agustian Setyagraha; Ida Kuntalasari; Dwi Imroatus Sholikah (Cerdika: Jurnal Ilmiah Indonesia, 2026)
This study examines the implications of international law on digital data ownership disputes between states and global corporations, focusing on the interaction among state sovereignty, multinational corporate responsibility, and the protection of individual digital rights. In the era of global digital integration, data has become a strategic asset that transcends national jurisdictions. The disparity between national regulations centered on data sovereignty and cross-border corporate operations has created a legal lacuna that weakens the position of states in protecting citizens’ data. Using a literature review method and a normative-comparative approach, this research explores several legal instruments such as the General Data Protection Regulation (GDPR), OECD Privacy Guidelines, and Indonesia’s Law No. 27 of 2022 on Personal Data Protection (PDP Law). The findings reveal the absence of a comprehensive international convention governing digital data ownership, resulting in overlapping jurisdictions, weak corporate accountability, and limited cross-border law enforcement. Moreover, technological developments that outpace legal adaptation have intensified digital human rights issues, particularly concerning the right to privacy and personal data control. The study emphasizes the importance of establishing harmonized international legal frameworks that balance the interests of states, corporations, and individuals through the principles of digital sovereignty, accountability by design, and cross-border cooperation mechanisms to ensure the protection of rights and data sovereignty in the era of global digitalization.